Den androgyne figur som ikon - Stinne Gunder Strøm Krogager (Akademisk Kvarter, 2015)
Lifestyle magazines do not just communicate consumer-oriented fashion and lifestyle in the fashion editorial. On the contrary, it often functions as a tool for the magazine to orchestrate its cultural identity and this way it can be perceived as the magazine’s work of art. As an autonomous work of art it involves the reader by a vast use of iconic references, which draws on a comprehensive variety of historical, literary, cultural as well as artistic icons, symbols and representations. These are staged delicately, ironically, sexualized and aesthetically and they function as a visual appetizer as well as a challenge of decoding for the reader. This article argues that the use of iconic representations mirrors the reader and his intellectual competence and this argument is based on an analysis of fashion photographs taken from a fashion editorial from the Danish lifestyle magazine for men, Euroman.